2007
DOI: 10.1029/2006jd007271
|View full text |Cite
|
Sign up to set email alerts
|

Ozonesonde observations in the Arctic during 1989–2003: Ozone variability and trends in the lower stratosphere and free troposphere

Abstract: We have studied the interannual and longer‐term variations in ozone profiles over the Arctic from 1989 to 2003 using ozonesonde observations from seven northern high‐latitude stations. The ozonesonde data have been carefully examined and made as internally consistent as possible. The homogenized measurements are analyzed with a statistical model. In both the stratosphere and troposphere the largest long‐term changes have occurred in the late winter/spring period (January–April), the period of greatest interann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 57 publications
13
111
1
Order By: Relevance
“…The motivation for this effort rests on characterizations of the precision and accuracy achievable with well-prepared ozonesondes through laboratory tests (Smit and Sträter, 2004a, b;Smit et al, 2007) and field tests (Kivi et al, 2007;Deshler et al, 2008). These results have shown that the precision of an ECC ozonesonde is better than observed systematic differences between ozonesonde type or solution concentration.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The motivation for this effort rests on characterizations of the precision and accuracy achievable with well-prepared ozonesondes through laboratory tests (Smit and Sträter, 2004a, b;Smit et al, 2007) and field tests (Kivi et al, 2007;Deshler et al, 2008). These results have shown that the precision of an ECC ozonesonde is better than observed systematic differences between ozonesonde type or solution concentration.…”
Section: Discussionmentioning
confidence: 91%
“…The first results comparing ozonesondes flown with 1.0 and 0.5 % KI cathode solution were based on only a few comparisons . More extensive results were obtained from comprehensive intercomparisons in the laboratory (Smit et al, 2007) and in the field (Kivi et al 2007;Deshler et al, 2008). These comparisons led to the current WMO recommendations for ECC ozonesonde preparations (Smit and ASOPOS Panel, 2014); however, between the mid1990s and late 2000s the ozonesonde community was using several combinations between 1.0 and 0.5 % KI cathode cell concentrations in SP and EN ozonesondes.…”
Section: Contributions Of Electrochemical Concentration Cell Ozonesonmentioning
confidence: 99%
See 2 more Smart Citations
“…An ozone excess over northwest Europe was already confined to the lower stratosphere in the earlier work from Mantis et al (1981). Kivi et al (2007) were studied the interannual and long-term variations in the ozone profiles over the Arctic from 1989 to 2003 . They found a mean secondary ozone maximum between the tropopause and the 150 hPa altitude during May and August.…”
Section: Introductionmentioning
confidence: 99%